Why Challenging Discrimination at Borders is Challenging (and Often Futile). (11th October 2021) - Cinnéide, Colm Ó
Abstract : International human rights law recognizes a general right to non-discrimination. This right has proved to have plenty of legal "bite." It is regularly invoked at both international and national levels to challenge state action which discriminates against vulnerable groups on "suspect grounds, " such as race, gender, and disability. Such legal challenges periodically succeed in generating significant law reform and sometimes even social change. However, this (relative) success has not been replicated when it comes to migration control. Non-discrimination challenges to state immigration restrictions have rarely been successful, even though human rights experts, NGOs, and other critics repeatedly express concern about the discriminatory impact of such restrictions. Furthermore, the state of human rights law remains radically underdeveloped in this area: the normative content of international non-discrimination norms, as they apply to migration control, is still lacking substance. This essay seeks to analyze why the cutting edge of the right to non-discrimination becomes blunted at the border, and generally lacks impact when invoked to challenge state migration controls.